Optimizing Bank Reconciliation Through the Utilization of SAP-Based Accounting Information Systems - Sitohang, Rony Marthin; Saepudin, Udin; Baridah, Wahyu Lailatul; Fikri, Muhammad Kanzul (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to determine how ERP systems, specifically SAP, are used to document bank reconciliation results. The method used is descriptive with a qualitative approach through direct observation and in-depth interviews. The results show that although the reconciliation process is still performed manually, SAP plays a significant role in systematic final recording, accelerating reporting, and improving the reliability of financial data. SAP implementation also helps minimize recording errors and supports more accurate decision-making.